A Differential Modulation Scheme for Metasurface-Based Terahertz Communications - Guo, Shuaishuai; Ye, Jia; Zhang, Peng (Frontiers in Communications and Networks, 2021)
Metasurface based terahertz (THz) modulators, which carry information by changing the spatial pattern of the metasurface at every symbol time, is an important component to establish low-cost low-energy-consumption THz communication systems. This paper proposes a differential spatial THz modulation (DSTM) scheme for metasurface assisted THz communications. In DSTM, the metasurface pattern activation orders are employed to carry information, instead of the metasurface patterns themselves. In this way, DSTM receiver can perform differential detection without knowing the metasurface response to incident THz signals and the channel state information. The proposed DSTM scheme is applicable to all kinds of metasurfaces enabled THz communications, including transmissive metasurfaces and reflective metasurfaces. For high-rate DSTM systems, we propose an efficient bits-to-activation-order mapping method and a low-complexity detection method. Simulations are conducted to demonstrate the performance of the proposed schemes. It is shown that the proposed scheme pays acceptable penalty compared to the non-differential modulation scheme with coherent detection, which needs to know the metasurface response to the incident signals as well as all the channel state information.